LINDANE TOXICITY IN A 7 YEAR OLD BOY - Daud, Yousaf; Rehman, Daud -ur-; Farooq, Umer (Journal of Ayub Medical College Abbottabad, 2010)
Lindane (gamma-benzene hexachloride) is widely used as a scabicide by general practitioners and dermatologists in Pakistan. We present a case of a 7 year old boy who had suffered from scabies 1 week ago, for which he was prescribed lindane along with other medications by a general practitioner. After 3 application of lindane the child began to experience Grand mal seizures, ataxia, weakness, incoordination and severe burning paresthesias. Lindane is known to cause neurotoxicity and for this it has been recommended as a 2nd line treatment for scabies by FDA. Keywords: lindane, scabicide, topical application, toxicity, adverse effects, neurotoxic, children